New information on trace fossils of the early Ordovician of Prague Basin (Barrandian area, Czech Republic) - Mikulas,R. (Journal of the Czech Geological Society, 1993)
Coarse-grained sandstones of the Trenice Formation (Tremadocian) at Jivina locality yielded trace fossils Bergaueria aff. langi and Skolithos ichnosp. Spirophycus cf bicornis and ?Urohelminthoida ichnosp. are described from clay shales of the Sarka Formation at Praha - Jeneralka locality. Oolitic iron ores at the base of this formation (Ejpovice locality) contain frequent Bergaueria aff. hemispherica, Phycodes ichnosp., Planolites beverleyensis. From the facies of fine-grained sandstones with intercalations of clay shales (Veliz locality) derive the finds of Didymaulichnus ichnosp. and Helminthopsis ichnosp. The Dobrotiva Formation (Dobrotivian Stage) yielded trace fossil assemblages from the Ejpovice locality (rhythmical alternation of sandstones and shales; Diplocraterion, Bergaueria, Isopodichnus, Phycodes, Planolites, Tomaculum), from Praha, Pelc-Tyrolka locality (siltstones, greywackes, fine-grained sandstones; Dictyodora, Zoophycos, Rhizocorallium), from Praha-Zizkov (Zoophycos) and from Praha - I.P. Pavlov's square (Phycodes).